2021
DOI: 10.5435/jaaosglobal-d-20-00159
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Progression to Surgical Release After Injection of Trigger Digits

Abstract: Introduction: The mainstay of trigger finger treatment is a corticosteroid injection of the affected digits and is associated with a very high success rate. However, some patients do not respond to nonsurgical management and undergo subsequent surgical release. The purpose of this study is to investigate the comorbidities that predispose patients to progressing from injection to surgical release. Methods: Patient data were obtained from a national insurance database. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Another cadaveric study (Hevesi et al., 2022) reported that the A1 and A2 pulley confluence was most commonly observed in the middle finger, which could also be a cause of failure of percutaneous release. The middle finger is also one of the risk factors for progression to surgical release after steroid injection (Kang et al., 2021). For this reason, it is thought that percutaneous release was performed most frequently in the middle finger in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Another cadaveric study (Hevesi et al., 2022) reported that the A1 and A2 pulley confluence was most commonly observed in the middle finger, which could also be a cause of failure of percutaneous release. The middle finger is also one of the risk factors for progression to surgical release after steroid injection (Kang et al., 2021). For this reason, it is thought that percutaneous release was performed most frequently in the middle finger in our series.…”
Section: Discussionmentioning
confidence: 99%
“…(1990) demonstrated that 49% of patients experienced resolution or notable improvement of symptoms following one injection, whereas the success incidence decreased to 23% after two injections and 5% after three injections. In addition, Kang et al. (2021) found that patients requiring multiple steroid injections are more likely to undergo surgical release.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most frequent affections in our specialty. It is more frequent in women after the fourth decade of life 7 , and the most affected fingers are the thumb, middle, and ring fingers.…”
Section: Trigger Fingermentioning
confidence: 99%